PHOTOSYNTHETIC PRODUCTIVITY OF PEAR TREES GROWN ON DIFFERENT ROOTSTOCKS - Bosa, K.; Jadczuk-Tobjasz, E.; Kalaji, M. H. (Annali di Botanica, 2016)
Since the pear is not a flagship crop in Polish orchards, very little advanced research is conducted to obtain knowledge about its photosynthetic productivity strategies. The research described in this paper involves measurements of the physiological state and yield of pear trees (cv. ‘Conference’) budded on different rootstocks. The main aim is to monitor the influence of budding on different rootstocks on photosynthetic productivity, growth, and yield of this cultivar, in order to improve agricultural practices for a sustainable horticulture. Leaf gas exchange, photosynthetic efficiency, leaf area index, and chlorophyll content were measured, as was tree yield. Our results provide better understanding of the physiological factors behind pear productivity.